Lexical Complexity of Students' Oral Performance on PechaKucha - Famala Eka Sanhadi Rahayu (Master Program in Linguistics, Diponegoro University, 2021)
This study examines the lexical complexity of undergraduate students' speaking performance, taking from their performance in Pechakucha. Pechakucha is an internet-based platform that enables people to do their presentations at a specific time and share it worldwide. The researcher uses PechaKucha since it enhances the students' actual speaking competence by giving them limited time to discuss an image. The lexical complexity of the students' speaking performance is measured using Lexical Complexity Analyser (LCA). This present study finds a significant difference between students' lexical frequency when performing descriptive and narrative oral presentations, shown by the sig.2-tailed of that variable is less than 0.05. While on the other hand, students' lexical variation, lexical density and lexical sophistication showed that the sig-2 tailed value is higher than 0.05, which means there is no significant difference between those two oral presentations. The finding indicates that the students' word choices are similar, and the measurements of their lexical complexity are influenced by the different requirements applied in two oral presentations. In addition, Pechakucha is one of the speaking activities which can be an alternative activity during online classes which prevent students from having face-to-face speaking activity.